2012
DOI: 10.5152/akd.2012.038
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of clinical and demographic characteristics and their association with length of hospital stay in patients admitted to cardiac intensive care unit with the diagnosis of acute heart failure

Abstract: Akut kalp yetersizliği nedeni ile kardiyoloji yoğun bakım ünitesine yatırılan hastaların klinik ve demografik özelliklerinin ve bu özelliklerin hastanede kalış süresi ile ilişkisinin incelenmesiEvaluation of clinical and demographic characteristics and their association with length of hospital stay in patients admitted to cardiac intensive care unit with the diagnosis of acute heart failure ABSTRACTObjective: Despite increasing incidence, data regarding clinical and demographic characteristics of patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…In this present study, compatible with the results of the previous studies, AF, higher creatinine and lower sodium were demonstrated to be associated with prolonged LOS independent from other factors (30,39,40). In addition, considering that the comorbidities increase with increased age, it is not surprising for LOS to be prolonged (30,41). While anemia demonstrated as an independent predictor for prolonged LOS in some studies, lower hemoglobin was significantly associated with prolonged LOS in the univariate analysis in the present study but It was demonstrated to lose its significance in the multivariate analysis (30,41).…”
Section: Wwweurjhscomsupporting
confidence: 81%
See 1 more Smart Citation
“…In this present study, compatible with the results of the previous studies, AF, higher creatinine and lower sodium were demonstrated to be associated with prolonged LOS independent from other factors (30,39,40). In addition, considering that the comorbidities increase with increased age, it is not surprising for LOS to be prolonged (30,41). While anemia demonstrated as an independent predictor for prolonged LOS in some studies, lower hemoglobin was significantly associated with prolonged LOS in the univariate analysis in the present study but It was demonstrated to lose its significance in the multivariate analysis (30,41).…”
Section: Wwweurjhscomsupporting
confidence: 81%
“…In addition, considering that the comorbidities increase with increased age, it is not surprising for LOS to be prolonged (30,41). While anemia demonstrated as an independent predictor for prolonged LOS in some studies, lower hemoglobin was significantly associated with prolonged LOS in the univariate analysis in the present study but It was demonstrated to lose its significance in the multivariate analysis (30,41). In this study, contrary to other previous studies on this subject, preadmission BB, ACEI/ARB, MRA, and diuretic use were also evaluated, and only BB use among all the drugs was found to be associated with prolonged LOS in both the univariate and multivariate analyses.…”
Section: Wwweurjhscommentioning
confidence: 99%
“…Whellan and colleagues' study 27 of 70,000 patients found that factors such as AF, COPD, DM, chronic renal failure, female sex, low systolic blood pressure, high heart rate, and low levels of hemoglobin, high levels of BUN, and high levels of brain natriuretic peptide were associated with prolonged LOS. Sahin and associates 38 found that low systolic blood pressure, high BUN, anemia, and severe mitral insufficiency at the time of admission were independently associated with LOS. In patients older than age 65 years, only female sex and poor functional class at the time of hospitalization were found to be correlated with LOS.…”
Section: Discussionmentioning
confidence: 99%
“…The recently published EURObservational Research Programme Heart Failure Pilot Survey demonstrated that the rate of 1-year mortality or rehospitalization was 36% in hospitalized HF patients and 18% in chronic HF patients ( 5 ). These large numbers, and repeated prolonged hospitalizations for HF, also create a substantial economic burden on the health care system ( 6 ). Therefore, HF requires special management strategies to overcome its worst clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%